Judicial Considerations on Legal Protection for Insurance Policyholders in Bankruptcy Cases of Insurance Companies: An Analysis of The Supreme Court Decision No. 408 K/Pdt.Sus-Pailit/2015 - Batubara, Beni Arbi (Rechtsvinding, 2025)
The bankruptcy of an insurance company represents a complex legal phenomen on that generates significant implications, particularly concerning the protection of policyholders’ rights. This situation demonstrates that, to date, the existing national regulatory framework has not yet been fully effective in anticipating the diverse legal consequences arising from the insolvency of insurance institutions. In practice, such circumstances often result in substantial financial losses for policyholders, primarily because the insurance premiums that have been paid during the validity of the insurance agreement become difficult to recover. This difficulty arises from the fact that the insolvent insurance company is legally incapable of fulfilling its contractual obligations. Consequently, the policyholders’ entitlement to the benefits of risk transfer an essential purpose of insurance cannot be realized as intended. Within the legal relationship between the policyholder and the insurance company, the policyholder occupies the position of a consumer who receives financial service benefits. As consumers, policyholders are entitled to legal protection against any actions, policies, or conditions that could potentially cause harm or loss. In this regard, policyholders, as consumers of financial services, possess a constitutional right to adequate legal protection, including in situations where the insurance company has been declared bankrupt. Such protection is essential to ensure that consumers’ rights are not disregarded and to maintain a fair balance between the interests of business actors and service users. Therefore, the government plays a crucial role in ensuring the establishment of an effective legal protection mechanism either through legislative instruments or regulatory oversight policies to safeguard policyholders from the adverse impacts of insurance company bankruptcy.